Formaldehyde Release From Eyelash Glues: Analysis Using the Chromotropic Acid Method. Issue 6 (8th November 2022) - Xiong, Michelle; Shaik, Javed A.; Hylwa, Sara
Abstract : Background: Popularity of eyelash enhancements has increased dramatically. Eyelash enhancements are available as an over-the-counter consumer product with glue included and as a professional product where proprietary glues are typically used. Both types of eyelash extension glues may release formaldehyde despite not being declared as an ingredient. Although formaldehyde is a carcinogen and may cause allergic contact dermatitis, few studies have assessed its presence in eyelash glues. Objective: The aim of the study was to evaluate professional and consumer eyelash glues for the presence of formaldehyde using the chromotropic acid method (CAM). Methods: A total of 37 eyelash glues were evaluated: 17 consumer eyelash glues (2 of which declared formaldehyde) and 20 professional eyelash glues (none of which declared formaldehyde) were purchased and analyzed with the CAM of testing. Results: For consumer eyelash glues, the 2 glues that declared formaldehyde were positive on CAM testing as well as 2 glues (13.3% [2/15]) that did not declare formaldehyde. Of the 20 professional eyelash glues, 15 (75.0%) were positive for formaldehyde. Conclusions: Some consumer eyelash glues and most professional eyelash glues released formaldehyde when evaluated with CAM. Patients and clinicians should be aware that both consumer and professional eyelash glues can be sources of formaldehyde.